In-Vitro Sunscreen Activity of White Turi Leaf Acetone (Sesbania grandiflora (L.) Pers.) Extract: Aktivitas Tabir Surya Ekstrak Aseton Daun Turi Putih (Sesbania grandiflora (L.) Pers.) Secara In-Vitro - Siroj, Muhammad Said Agil; Rohmah, Jamilatur (Universitas Muhammadiyah Sidoarjo, 2020)
Sunscreens are cosmetic preparations that protect the skin from exposure to UV radiation resulting in erythema , skin burning , aging and skin cancer. Leaf of Sesbania grandiflora (L.) Pers. contain phenolic compounds such as tannins and flavonoids which act as photoprotective . This research method is experimental with quantitative descriptive analysis. The purpose of research is to know the value of SPF, transmission erythema (% Te) and pigmentation (% Tp) of acetone extracts of Sesbania grandiflora (L.) Pers. using Spectrophotometry UV -Vis at a wavelength of 280-400 nm with intervals of 5 nm. This study variations in extract concentration were made 100, 200, 400, 600, 800 and 1000 ppm. The results showed the SPF value of extracts of all concentrations in a row was 1.9 ( minimum ); 3.6 ( minimum ); 15.9 ( moderate ); 56.3 ( high ); 133.9 ( high ); and 136.6 ( high ). The %Te value is 400 ppm ( fast tanning ), 600 ppm ( regular suntan ) and 1000 ppm ( extra protection ). The value of %Tp at all extract concentrations is included in the category total block .